2021
DOI: 10.3390/cancers13184731
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib in Recurrent Glioblastoma Patients: A Large and Monocentric Real-Life Study

Abstract: Despite multimodal treatment with surgery and radiochemotherapy, the prognosis of glioblastoma remains poor, and practically all glioblastomas relapse. To date, no standard treatment exists for recurrent glioblastoma patients and traditional therapies have showed limited efficacy. Regorafenib is an oral multi-targeted tyrosine kinase inhibitor showing encouraging benefits in recurrent GBM patients enrolled in the REGOMA trial. We performed a large study to investigate clinical outcomes and the safety of regora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 32 publications
5
47
2
2
Order By: Relevance
“…Known therapy-limiting side effects with regorafenib include the occurrence of hand-foot skin reaction (HFSR), arterial hypertension, and elevations in lipase and bilirubin, whereas with lomustine therapy, hematologic toxicity is a particularly prominent side effect [10]. The same side effect profile was reported with regorafenib treatment in glioblastoma, but occurrence of °III and IV HFSR, hypertension, and fatigue was lower as described for patients with colorectal carcinoma in CORRECT trial [6,10,11]. It is expected, that these side effects occur more frequently, when regorafenib is used after several lines of systemic treatment compared to patients in the REGOMA trial who were treated in 2nd line with regorafenib.…”
Section: Introductionmentioning
confidence: 83%
“…Known therapy-limiting side effects with regorafenib include the occurrence of hand-foot skin reaction (HFSR), arterial hypertension, and elevations in lipase and bilirubin, whereas with lomustine therapy, hematologic toxicity is a particularly prominent side effect [10]. The same side effect profile was reported with regorafenib treatment in glioblastoma, but occurrence of °III and IV HFSR, hypertension, and fatigue was lower as described for patients with colorectal carcinoma in CORRECT trial [6,10,11]. It is expected, that these side effects occur more frequently, when regorafenib is used after several lines of systemic treatment compared to patients in the REGOMA trial who were treated in 2nd line with regorafenib.…”
Section: Introductionmentioning
confidence: 83%
“…Previously, a randomized, multicenter, open-label phase 2 trial (REGOMA) indicated enhanced efficacy of regorafenib compared to CCNU in recurrent GBM patients [ 224 ]. These findings were further supported by a retrospective clinical study analyzing the clinical outcomes of recurrent GBM patients receiving regorafenib outside clinical trials [ 225 ].…”
Section: Drug Repurposing For Glioblastomamentioning
confidence: 63%
“…These results, significantly different from the landmark REGOMA trial, may be due to distinct patient characteristics: both included noteworthy heterogenous populations both in prior recurrences (ranging from first to seventh) and in diagnosis including astrocytomas, oligodendrogliomas, and diffuse midline gliomas. A 2021 retrospective study [ 9 ], enrolling 54 patients treated with regorafenib showed similar mPFS (2.3 months) and OS (10.2 months) to the ones in the REGOMA trial.…”
Section: Discussion Real-life Data and Future Perspectivesmentioning
confidence: 93%